PEMENUHAN HAK ANAK PASCA PERCERAIAN PERSPEKTIF KOMPILASI HUKUM ISLAM DAN UU NO. 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK (Studi Kasus di Desa Kendaldoyong Kecamatan Petarukan Kabupaten Pemalang) - Ahmad Nurofik; Abdullah Afif (CV. KAMPUS AKADEMIK PUBLISING, 2024)
When a divorce occurs, the relationship between children and parents is not broken. They still have to fulfill their children's rights, both internal and external support. In Kendaldoyong village, Petarukan subdistrict, Pemalang district, many children are raised by their grandmothers after their parents' divorce. It is not uncommon for the child's living expenses to be borne by the grandmother. Where it should be borne by the biological father and mother. even though all child protection is regulated in law. This certainly has a bad impact on the future of the child who should be able to grow up happily with his family. For this reason, researchers are interested in researching it, aiming to find out how children's rights are fulfilled after divorce in Kendaldoyong Village according to Law No. 35 of 2014 concerning child protection and KHI (Compilation of Islamic Law) and find out the factors in which children's rights are not fulfilled after divorce. divorce in Kendaldoyong village, Petarukan subdistrict, Pemalang district. The research approach used in this research is qualitative, with data collection methods, namely observation, interviews and documentation which aims to ensure that the researcher is truly researching the existence of divorce. The location of this research is in Kendaldoyong village, Petarukan subdistrict, Pemalang Regency. With 4 sources from grandmothers who took care of the victim's children after the divorce and 3 from community figures. From the results of this research, it was concluded that first: in practice, many parents in Kendaldoyong village still neglect their responsibilities to fulfill the rights that children should receive in accordance with those regulated in the Compilation of Islamic Law (KHI) and Law N0.35 of 2014 About Child Protection. Second: the factors that cause parents in Kendaldoyong village to neglect their obligations include low economic conditions, low education, local community habits and lack of parental awareness.